Reduction of cardiac imaging tests during the COVID-19 pandemic: The case of Italy. Findings from the IAEA Non-invasive Cardiology Protocol Survey on COVID-19 (INCAPS COVID). (15th October 2021) - Dondi, Maurizio; Milan, Elisa; Pontone, Gianluca; Hirschfeld, Cole B.; Williams, Michelle; Shaw, Leslee J.; Pynda, Yaroslav; Raggi, Paolo; Cerci, Rodrigo; Vitola, Joao; Better, Nathan; Villines, Todd C.; et al.
Abstract: Background: In early 2020, COVID-19 massively hit Italy, earlier and harder than any other European country. This caused a series of strict containment measures, aimed at blocking the spread of the pandemic. Healthcare delivery was also affected when resources were diverted towards care of COVID-19 patients, including intensive care wards. Aim of the study: The aim is assessing the impact of COVID-19 on cardiac imaging in Italy, compare to the Rest of Europe (RoE) and the World (RoW). Methods: A global survey was conducted in May–June 2020 worldwide, through a questionnaire distributed online. The survey covered three periods: March and April 2020, and March 2019. Data from 52 Italian centres, a subset of the 909 participating centres from 108 countries, were analyzed. Results: In Italy, volumes decreased by 67% in March 2020, compared to March 2019, as opposed to a significantly lower decrease ( p  < 0.001) in RoE and RoW (41% and 40%, respectively). A further decrease from March 2020 to April 2020 summed up to 76% for the North, 77% for the Centre and 86% for the South. When compared to the RoE and RoW, this further decrease from March 2020 to April 2020 in Italy was significantly less ( p  = 0.005), most likely reflecting the earlier effects of the containment measures in Italy, taken earlier than anywhere else in the West. Conclusions: The COVID-19 pandemic massively hit Italy and caused a disruption of healthcare services, including cardiac imaging studies. This raises concern about the medium- and long-term consequences for the high number of patients who were denied timely diagnoses and the subsequent lifesaving therapies and procedures. Highlights: Cardiac imaging decreased by two-thirds in Italy in the early COVID 19 pandemic as the fight against COVID-19 was prioritized. The findings raise concern as cardiovascular diseases remain the main cause of death in the country, as well as worldwide. The lengthier procedures were most impacted and those where the risk of exposure to COVID-19 infections could increase. Exercise stress test, for example, where droplets of sweat and saliva are released in the air, was the most disrupted. This study underlines the fragility of healthcare systems to deliver lifesaving cardiac care under stressed conditions. The importance of supporting these systems with equipment, training, and infrastructure is underscored. The disruption caused by COVID-19 also impact strides of the past decades as regards decline in heart disease mortality.